The biogeography of fermentative yeast populations from the vineyards of the Azores archipelago - Neves, J. Drumonde (2011)
During the harvests of 2009 and 2010, 163 musts were obtained from grape samples collected in eight islands of the Archipelago of the Azores. The sampling plan included traditional and hybrid grape varieties from vineyards in appellations of origin and abandoned vineyards. In 2009, 2640 yeast isolates were obtained from the initial stage of fermentation, belonging to more than 20 species. Differences between most representative yeast species were apparent between islands, grape varieties, and the kind of vineyard. From the final fermentative stages, a total of 2850 isolates were obtained (1470 and 1380 in 2009 and 2010, respectively), whereas 1770 isolates were assigned to the species Saccharomyces cerevisiae. These isolates were classified in 275 strains (168 in 2009 and 107 in 2010). The percentage of S. cerevisiae and the number of strains per fermentation showed differences between islands, type of vineyard and sampling year.